The Contemporary Ushul Fiqh in Indonesia: An Idea and Practice - Ahmad Rajafi (Jurnal Ilmiah Al-Syir'ah, 2023)
This research explains the theory of Ushul Fiqh, which must live and not stagnate for Indonesia's benefit. Many of the study sources used as references come from Arabic-language books. A scientific study is needed that is more specific and shows the specificity of the Indonesian Ushul Fiqh model. This research method is a literature review by studying Ushul Fiqh in the Indonesian context. The results found are that the primary materials in the theory of Ushul Fiqh in Indonesia are always alive and experiencing evolution, starting from the implementation of established Ushul Fiqh products during the time of classical scholars to the birth of new theories which expected to be able to become new alternatives that responsive in answering the problems of the people who are also constantly moving and experiencing change. The theory of Ushul Fiqh implemented in the field by Indonesian scholars, such as the actualization of maqashid shariah in the Indonesian context, the flow of inculturation of revelation and local culture ilhaq al-masail bi nazhairiha, practicing qauli and manhaji Schools, and also making ijtihad plural or collective as the right solution for Indonesia as a form of prudence (ihtiyath) of the clergy.